Perceived barriers to ChatGPT integration in Islamic studies education: Insights from Malaysian international students in Indonesia - Darmu'in, Darmu'in; Nasikhin ,; Darnoto,; Sofanudin, Aji; Maarif, Muhammad Anas; Haryanto, Joko Tri (Journal of International Students, 2025)
This study explores the factors that limit Malaysian international students’ interest in using ChatGPT as a learning tool for Islamic Studies in Indonesia. Employing a qualitative narrative inquiry design, data were collected through in-depth interviews with students who possess Islamic educational backgrounds. The findings indicate three key barriers. First, participants perceive ChatGPT as lacking scholarly authority and a valid chain of transmission (sanad), which is essential in legitimizing religious knowledge. Second, students reported concerns about the tool’s limited ability to present accurate and contextualized religious evidence (dalil), requiring further verification from trusted sources. Third, apprehension arose regarding potential distortions in interpreting the Quran and Hadith, as proper exegesis requires mastery of Arabic, a thorough understanding of historical context, and adherence to established methodologies.